Discrete and Combinatorial Mathematics : An Applied Introduction - Grimaldi, Ralph P. ([S.l.] : Pearson, 2007)
Provides an introductory survey in both discrete & combinatorial mathematics. Intended for the beginning student designed to introduce a wide variety of applications & develop mathematical maturity of the student by studying an area that is so different form the traditional coverage in calculus & different equations. DLC: Mathematics.
Hardcover.
Keywords: Mathematical theory of computation; Algebra; Computer Mathematics; Science/Mathematics.; Combinatorics; Discrete Mathematics; Combinatorial analysis; Computer science; Mathematics